From Repetitive Head Trauma to Neurodegeneration: A Comprehensive Review of CTE - Piotraszewska, Marta; Skudzińska, Magda; Bartold , Magdalena; Grys , Maria Irena; Kochański , Filip; Pohrybieniuк, Janina; Wołk , Karolina; Jaskulska , Aleksandra; Pietrzak , Jan; Błonka , Dominika (Quality in Sport, 2025)
Chronic Traumatic Encephalopathy (CTE) is a progressive neurodegenerative disorder that arises due to repetitive head trauma. Initially identified in boxers as “dementia pugilistica,” it is now recognized as a nosological entity affecting various occupational and social groups, including contact sports athletes, military personnel, and victims of domestic violence. The ante-mortem diagnosis of CTE remains a significant clinical challenge, as current definitive diagnosis relies exclusively on post-mortem neuropathological examination, characterized by deposits of hyperphosphorylated tau protein, their specific distribution, and associated neuroinflammatory and degenerative alterations. Extensive research is underway to identify fluid biomarkers (e.g., NfL, p-tau, GFAP, UCH-L1, S100B) and neuroimaging modalities (e.g., PET, MRI, DTI) that may enable in vivo detection of CTE and differential diagnosis from other tauopathies. The clinical phenotype of CTE is highly heterogeneous, encompassing cognitive, behavioral, affective, and motor disturbances. Emerging evidence suggests the existence of neuropathological subtypes of CTE, which holds relevance for biomarker development and therapeutic strategies. This review synthesizes current knowledge on the molecular pathogenesis, established neuropathological criteria, epidemiology, clinical manifestations, biomarkers, and neuroimaging modalities of CTE, as well as contemporary therapeutic and preventive approaches. The manuscript highlights the diagnostic and therapeutic challenges and underscores the need for further research to develop effective ante-mortem diagnostic tools and treatment strategies for CTE.